Bilateral External Torque CT Reliably Detects Syndesmotic Lesions in an Experimental Cadaveric Study - Silvan Beeler MD; Esteban Ongini; Bettina Hochreiter MD; Reto Sutter MD; Arnd Viehoefer; Stephan H. Wirth MD; Anna-Katharina Calek MD (Foot & Ankle Orthopaedics)
Category: Sports; Trauma Introduction/Purpose: If tibiofibular syndesmosis injury is missed, chronic instability may lead to persistent pain and osteoarthritis. So far, no reliable diagnostic method has been available. The primary objectives of this study were to determine whether defined lesions of the syndesmosis can be correlated with specific tibiofibular joint displacements caused by external rotation (ER) torques and to compare its performance with arthroscopy. Secondary objectives included evaluation of Intraclass-Correlation-Coefficients (ICCs) and suitability of the healthy contralateral ankle as a reference. Methods: Seven pairs of healthy lower legs were tested and assigned to two groups (1) Supination-ER (SER) and (2) Pronation-ER (PER). In the intact state and after each surgical step, an ankle arthroscopy and three CT scans were performed. During the scans, the specimens were placed in an external torque device with 2.5Nm, 5Nm and 7.5Nm. Results: The arthroscopic and radiological parameters showed significant correlations in all pairwise comparisons. The receiver operating curve (ROC) analyses yielded best prediction of syndesmotic instability with the anterior tibiofibular distance (AD) on CT with a sensitivity of 84.1% and a specificity of 95.2% (area under the curve (AUC) 94.8%, CI 0.916-0.979, p< 0.0001) and middle tibiofibular distance at arthroscopy with a sensitivity of 76.2% and specificity of 92.3% (AUC 91.2%, CI 0.837-0.987, p< 0.0001). Higher torques increased the rate of true positive results. Conclusion: Bilateral external torque CT reliably detects experimental syndesmotic rotational instability compared to the healthy side with greater sensitivity and similar specificity to the arthroscopic lateral hook test. Translation of these experimental findings to clinical practice remains to be established.